Model Vehicle Routing Problem dengan Karakteristik Rute Majemuk, Multiple Time Windows, Multiple Products dan Heterogeneous Fleet untuk Depot Tunggal - Ary Arvianto; Aditya Hendra Setiawan; Singgih Saptadi (Institute of Research and Community Outreach - Petra Christian University, 2014)
In this paper we developed a VRP model for multiple routes, multiple time windows for multiple products and heterogeneous vehicles. The solution were constructed using a heuristic approach, i.e, a sequential insertion algorithm. Additionally, this model is applied to solve fuel distributions for eight customers in East Nusa Tenggara. It needs two tankers with capacity of 4700 kilo liters, so that those distributions can be accomplished with a minimum number of vehicles, total completion time, and range of completion time. The result of this study shows that for a heterogeneous vehicles problem, a vehicle with the largest capacity may not necessarily be the vehicle that provides an optimal solution. Moreover, advance trials should be conducted by providing a limited number of tankers for each tanker capacity, so the description of heterogeneous vehicles becomes more visible. In the future research, the solution will be improved by utilizing relocation techniques.